Host cell cAMP-Epac-Rap1b pathway inhibition by hawthorn extract as a potential target against Trypanosoma cruzi infection - Ferri, Gabriel (2023)
Although the two drugs currently available for the treatment of Chagas disease, Benznidazole and Nifurtimox, have proven to be effective in the acute phase of the disease, the 60–90-day treatment leads to high toxicity and unwanted side effects, presenting, in addition, a low efficacy in the chronic phase of the disease. For this reason, new therapies that are more effective are needed. In this regard, we have recently shown that the inhibition of the Epac-Rap1b pathway suppressed the cAMP-mediated host cell invasion by Trypanosoma cruzi. Interestingly, it has been described that vitexin, a natural flavone that protects against ischemia–reperfusion damage, acts by inhibiting the expression of Epac and Rap1 proteins. Vitexin can be found in plants of the genus Crataegus spp., traditionally known as hawthorn, which are of great interest considering their highly documented use as cardio-protectors. Pre-treating cells with an extract of Crataegus oxyacantha produced levels of T. cruzi invasion comparable to the ones observed for the commercially available Epac1-specific inhibitor, ESI-09. In addition, extract-treated cells exhibited a decrease in the activation of Rap1b, suggesting that the effects of the extract would be mediated by the inhibition of the cAMP-Epac-Rap1 signaling pathway. Using HPLC-HRMS2, we could confirm the presence of vitexin, and other flavones that could act as inhibitors of Epac/Rap1b, in the extracts of C. oxyacantha. Most significantly, when cells were treated with the extract of C. oxyacantha in conjunction with Nifurtimox, an increased modulation of invasion was observed.